Anaesthesia for Caesarean Section in a Jehovah’s Witness with Antepartum Haemorrhage: A Case Report - Okubuiro, Eze Onyegbule; Okoli, Chinwe Edith (International Journal of Innovative Research in Medical Science, 2019)
FN, a 29-year-old gravida 3 Para 2+2 female (with no live child), member of Jehovah’s Witness sect had emergency Caesarean section under general anaesthesia with endotrachael intubation for abruptio placentae at 35 weeks of gestation. Preoperative and postoperative packed cell volume (PCV) was 28% and 9% respectively. She received erythropoietin and iron dextran infusions. Patient developed anaemic heart failure on 3rd post-operative day which was managed successfully. She recovered completely and was discharged home on the 28th post-operative day. Management dilemmas specific to the Jehovah’s Witness parturient with abruptio placentae are discussed.